Educação escolar: práticas docentes e emancipação humana em Icapuí - CE (1980-1990) - Oliveira, Renata Tavares de (2022)
The present research approaches how the teaching performance took place, praised school performance, in the early 1990s, in the face of the process of emancipation of the municipality of Icapuí, located in the state of Ceará, focusing on the historical educational development of the community. The school performance of the municipality received several awards aimed at quality education and reflective character, becoming a highlight in the international scope. To better understand the school success that took place in the municipality, it was necessary to analyze its teaching role, identifying factors that contributed to its educational growth. In this sense, this investigation showed an understanding of how the teaching performance enhanced the school performance of the municipality of Icapuí, in the 1990s. Relating the teachers' conception of school, through their social and academic formation. The methodology was based on the bibliographic study, in addition to semistructured interviews with teachers who worked throughout this educational development process, as well as public managers who participated in this socio-historical path. To support this research, authors who work from the perspective of the historical and political rescue of the history of the municipality were used, with emphasis on education and teaching. Silva (1998) articulates political representation with the movement of struggle for emancipation. Regarding the education of the municipality, Paulo Freire comes with the perspective of dialogicity, creating conditions for the construction of the emancipation and autonomy of the individual. Authors such as Antonio Nóvoa (1995), Paulo Freire (2019) and Demerval Saviani (1996), guided the reflections on the teachers' narratives about school success and teaching protagonism, expanding the discussion and allowing it to be possible to see the researched subjects as authors of their own stories. In this perspective, it is necessary to know the school formation in the municipality, evidencing the possible feeling of belonging, it is listed with the concept of education about the subject, so that it is not just a transmitter of information, acting as a professional capable of transforming stories and emancipating thoughts.